Solusi Persamaan Schrödinger untuk Potensial Hulthen + Non-Sentral Poschl-Teller dengan Menggunakan Metode Nikiforov-Uvarov - Nani Sunarmi; Suparmi S; Cari C (Department of Physics, Sebelas Maret University, 2016)
The Schrödinger equation for Hulthen potential plus Poschl-Teller Non-Central potential is solved analytically using Nikiforov-Uvarov method. The radial equation and angular equation are obtained through the variable separation. The solving of Schrödinger equation with Nikivorov-Uvarov method (NU) has been done by reducing the two order differensial equation to be the two order differential equation Hypergeometric type through substitution of appropriate variables. The energy levels obtained is a closed function while the wave functions (radial and angular part) are expressed in the form of Jacobi polynomials. The Poschl-Teller Non-Central potential causes the orbital quantum number increased and the energy of the Hulthen potential is increasing positively.